Osmotic power plant in the Agno River-Lingayen Gulf Delta System, Philippines a plant design - Esguerra, Jasper Powell S.; Gernan, Diana Joy P.; Parrocha, Vergelle A.; Ramoso, Patrick D.; De Leon, Rizalinda L. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
In the world today, where current energy sources are expensive, harmful to environment, and in the near future, limited, there is a search for clean, renewable, and cheap fuel alternative and one of the most promising renewable resources is biodiesel. Since the institution of the Act of 2006, a 2 percent biodiesel blend is required in all diesel products thus, increasing the demand, especially in the near future where there will also increase in the biodiesel blend. The general objective of this study is to design the first biodiesel production plant in the country that uses two-step heterogeneous catalysis that is efficient, economical, and environmental-friendly, and produce high-value products using low-value raw materials.Since 2010, the Philippines consumes more biodiesel than it produces. With this, and the projected increase in demand in the future, there is a need for a new biodiesel plant. Through there are many current biodiesel players, the proposed biodiesel plant aims to compete with these companies by being able to supply the same quality of biodiesel at a cheaper price by using cheaper raw materials and using a more efficient production process. The biodiesel plant, which will be located in Valenzuela City will use waste cooking as raw materials and metakaolinite and calcium oxide as esterification and transesterification catalyst, respectively. The two-step catalysis can lower the biodiesel production cost because of easier catalyst separation and reusability of the catalyst. Ester yield will be higher because free fatty acids will also be converted to biodiesel.The plant will be divided into four blocks namely: (1) Storage and Reaction; (2) Separation; (3) Glycerine Purification; and, (4) Utility and Waste water treatment. The plant will need cooling water and saturated steam as utilities and 19, 400 MJ/ada of power. Important equipment are the Esterification Reactor, transforms free fatty acid into biodiesel, Transesterification, transforms triglycerides into biodiesel, Washing Column, purifies biodiesel product into commercial grade, Falling Film Evaporator, removes water and methanol from the glycerine, Flash Drum, purifies glycerine into commercial grade, and distillation column, separates residual methanol and water.
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design.
Keywords: Hydroelectric power plants -- Philippines; Osmotic power